Role of Ba in low temperature thermochemical conversion of carbon dioxide with LaFeO3 perovskite oxides. Issue 51 (September 2021) - Shi, Hanzhong; Bhethanabotla, Venkat R.; Kuhn, John N.
Highlights: Low temperature CO2 to CO conversion by perovskite oxide materials La1-x Bax FeO3 . Stabilized perovskite catalyst structure during redox reaction. La0.4 Ba0.6 FeO3 is the optimal composition for balancing CO yield and catalyst stability. Surface reaction modeled as adsorbed CO2 γ− dissociated to CO and O. Abstract: Reverse water-gas shift chemical looping (RWGS-CL) is a low temperature thermochemical process to convert CO2 to CO by perovskite oxides. In this research, perovskite oxides of the form of La1- x Ba x FeO3 ( x = 0.25−0.75) are explored for enhancing CO yield while maintaining stability over multiple cycles. DFT was utilized to calculate the oxygen vacancy formation energies (Evac ) identifying Evac of La0.75 Ba0.25 FeO3 (3.3 eV) and La0.5 Ba0.5 FeO3 (3.0 eV) are in the ideal range of 3.4 ± 0.5 eV. Additional Ba resulted in instability. XRD confirmed cubic perovskite structure and XRF analysis established the precise composition. XPS revealed that the materials had Ba enrichment at the surface, compared to the overall bulk. Temperature-programmed reduction (TPR) and oxidation (TPO) experiments determined that CO2 is converted to CO in the low temperature range of 400–600 °C for all compositions, which is lower than temperatures of many thermochemical CO2 processes. Isothermal cycling between hydrogen and CO2 at 600 °C indicated La0.5 Ba0.5 FeO3 and La0.4 Ba0.6 FeO3 were stable (verified by XRD and XPS) and produced CO at high yields of 200 and 500 μmol/gLBF, respectively. The CO2 conversion step fits to Langmuir–Hinshelwood type kinetics based on its partial pressure dependency and is consistent with DRIFTS studies. Therefore, multiple materials in this study enhance performance, indicating their suitability for industrial scale adaptation upon energy integration as a possible strategy for renewable energy storage in chemical form.